Parasitic castration: the evolution and ecology of body snatchers - Lafferty, Kevin D.; Kuris, Armand M. (Trends in parasitology, 2009)
Castration is a response to the tradeoff between consumption and longevity faced by parasites. Common parasitic castrators include larval trematodes in snails, and isopod and barnacle parasites of crustaceans. The infected host (with its many unique properties) is the extended phenotype of the parasitic castrator. Because an individual parasitic castrator can usurp all the reproductive energy from a host, and that energy is limited, intra- and interspecific competition among castrators is generally intense. These parasites can be abundant and can substantially depress host density. Host populations subject to high rates of parasitic castration appear to respond by maturing more rapidly.